La didattica della letteratura nell’epoca della sua riproducibilità digitale: i prezzi della «transizione» - Emanuele Zinato (Laboratoire Italien, 2022)
The article consists of a pars destruens and a pars construens. The first part involves a critical examination of the prominent terms in the current ideology of governance and their impact on the management of digital education today. The second part includes an analysis of literature teaching in the context of digital transformation and a paradoxical proposal of Benjaminian resistance focused on the “proper use” of literary fragments in hostile educational situations.